Recognizing and correcting developing malocclusions : a problem-oriented approach to orthodontics - Araújo, Eustáquio A. (Eustáquio Afonso), 1946-; Buschang, Peter H. (Peter Heinz), 1951- (Wiley Blackwell, 2016)
Recognizing and Correcting Developing Malocclusions: A Problem-Oriented Approach to Orthodontics provides an evidence-based approach to early treatment, an often-controversial topic. Based on decades of experience in clinical practice and education, Drs. Araújo and Buschang clearly present treatment protocols for mixed-dentition patients with various malocclusions and other orthodontic problems. Class I, Class II, and Class III malocclusions are covered extensively, along with eruptive deviations and open-bite malocclusions. The literature is comprehensively reviewed to ensure that the reader thoroughly understands the development, phenotypic characteristics and etiology of each type of malocclusion. Taking a problem-oriented approach, the authors provide detailed information for each case, develop comprehensive problem lists, and then provide evidence-based treatment solutions. The clinical focus of the text is ideal suited for private-practice clinician, with numerous references and academic underpinnings to ensure its suitability for orthodontic and pediatric dentistry residents.-Focuses solely on mixed dentition orthodontic treatments -Great variety of case studies--5 to 10 cases per chapter -Each case is presented in the format of a problem list and evidence-based solutions -More than 300 clinical photographs and radiographs.